Sleep disorders in Prader-Willi syndrome, evidence from animal models and humans. (June 2021) - Cataldi, Matteo; Arnaldi, Dario; Tucci, Valter; De Carli, Fabrizio; Patti, Giuseppa; Napoli, Flavia; Pace, Marta; Maghnie, Mohamad; Nobili, Lino
Summary: Prader-Willi Syndrome (PWS) is a complex genetic disorder with multiple cognitive, behavioral and endocrine dysfunctions. Sleep alterations and sleep disorders such as Sleep-disordered breathing and Central disorders of hypersomnolence are frequently recognized (either isolated or in comorbidity). The aim of the review is to highlight the pathophysiology and the clinical features of sleep disorders in PWS, providing the basis for early diagnosis and management. We reviewed the genetic features of the syndrome and the possible relationship with sleep alterations in animal models, and we described sleep phenotypes, diagnostic tools and therapeutic approaches in humans. Moreover, we performed a meta-analysis of cerebrospinal fluid orexin levels in patients with PWS; significantly lower levels of orexin were detected in PWS with respect to control subjects (although significantly higher than the ones of narcoleptic patients). Sleep disorders in humans with PWS are multifaceted and are often the result of different mechanisms. Since hypothalamic dysfunction seems to partially influence metabolic, respiratory and sleep/wake characteristics of this syndrome, additional studies are required in this framework.